The effects of art design courses in higher vocational colleges based on C-STEAM - Qian, Chen; Ye, Jian-Hong; Lee, Yi-Sang (Frontiers in Psychology, 2022)
C-STEAM education is aimed at preserving local culture, while also improving students’ interests and skills in science, technology, engineering, art, and mathematics-related fields. Other goals are to cultivate students to solve complex and practical problems through interdisciplinary thinking or integrate learning subjects with local senses in the context. In the present curriculum implemented in China, STEAM education mainly focuses on K-12 education and kindergarten education, and it is not widely implemented in colleges and universities, and most of the existing courses are carried out in general technical courses such as robotics and 3D printing, and less in design courses, since the concept of STEAM education has just begun to be advocated recently. Nevertheless, STEAM courses are still limited to special educational systems and disciplines, even though these courses have been vigorously promoted in China. Thus, this study designed an innovative higher vocational college curriculum based on the interdisciplinary principle of C-STEAM, using art design as a meta-theme framework and integrating Chinese local culture. A single-subject quasi-experimental design method was used. A total of 45 students majoring in art design in a higher vocational college were invited to participate in this study. The teaching experiment lasted for 9 weeks. Through teachers’ teaching and, demonstration and students’ independent learning of C-STEAM knowledge in the field of art and design, the concept of C-STEAM was introduced to the creation of packaging design. At the same time, a model composed of six hypotheses was constructed, using the creative self-efficacy scale, learning engagement scale, and creative performance assessment as measurement methods, to discuss students’ participation in the art and design courses of higher vocational colleges based on the concept of C-STEAM integration of creative self-efficacy, learning engagement, and creative performance over time. The results showed that students with higher creative self-efficacy had higher learning engagement (cognitive, affective, and behavioral), and students with higher learning engagement performed better in terms of creative performance. The results of this study can help researchers and educators to focus on C-STEAM courses and provide suggestions for the cultivation of art and design professionals in higher vocational colleges.